Applications of electrical tomography to improve the performance of crystallization, precipitation and mixing processes - Synopsis - K. M. Primrose (The Southern African Institute of Mining and Metallurgy, 2008)
Electrical tomography has developed rapidly over the last few years in its sophistication and practical use to enable three-dimensional information on the distribution of phases within flowing mixtures to be observed1. This paper reviews the current state of application from the industrial perspective, drawing on applications case studies based on scaling studies in the laboratory right through to installations on plant. In the laboratory, applications have looked at scale-up of mixing2 processes involving gas-liquid and solid-liquid suspensions3 with a particular interest in verifying computational fluid dynamics simulations or in checking scale-up design4,5. In the processing plant, the circumstances are usually bespoke and may range from simple detection of the degree of homogeneity of a flowing mixture through to the need to measurement a sophisticated batch process such as crystallization, sedimentation, filtering and drying. Examples drawn from the chemical and pharmaceutical industries will be presented and related to the benefits that can be gained through application of the method.